The influence of grammar on english learners’ writing accuracy at the School of Modern Languages - Córdoba Cubillo, Patricia (Universidad de Costa Rica. Campus Rodrigo Facio. Sitio web: https://www.ucr.ac.cr/ Teléfono: (506) 2511-4000. Correo de soporte: revistas@ucr.ac.cr, 2015)
This article presents the results of a study conducted in three English courses of the curriculum of the B.A. in English and the B.A. in English Teaching from the School of Modern Languages at the University of Costa Rica. The objective of this investigation was to determine whether the teaching of grammar contents, according to the students’ perceptions, helped them to develop their writing accuracy in their first two composition courses. In order to determine if the students’ opinions were congruent with their grammar accuracy, some of their writing samples were analyzed. The results show that there was no congruence in some areas.